O modelo brasileiro de direito administrativo sancionador: do processo civil sancionador ao ne bis in idem - Xavier, Marília de Araújo Barros (2022)
The study of ne bis in idem is one of the themes that have worried jurists around the world, given the presence of the State in societies as a manager of security in countless scenarios. It is also a matter of outstanding complexity, both practical and theoretical, with interfaces in procedural law, criminal law, public international law, community law and, more recently, administrative law. In Brazil, this study has a peculiarity: the legislator's choices. From our constitutional provisions on the protection of probity, the prohibition of bis in idem, which includes administrative law, can only be understood in the study of the process; is a sign of our culture: the Brazilian model, where, we dare say, the double sanctioning process does not violate the ne bis in idem, for all administrative law, imposing the discount technique. The result is a greater demonstration of what it is: the Brazilian model of sanctioning administrative law